Associative and Identity Words Promote the Speed of Visual Categorization: A Hierarchical Drift Diffusion Account - Todorova, Lara; Neville, David A. (Frontiers in Psychology, 2020)
Words can either boost or hinder the processing of visual information, which can lead to facilitation or interference of the behavioural response. We investigated the stage (response execution or target processing) of verbal interference/facilitation in the response priming paradigm with a gender categorization task. Participants in our study were asked to judge whether the presented stimulus was a female or male face that was briefly preceded by a gender word either congruent (prime: ‘man’, target: ‘man’), incongruent (prime: ‘woman’, target: ‘man’) or neutral (prime: ‘day’, target: ‘man’) with respect to the face stimulus. We investigated whether related word-picture pairs resulted in faster reaction times in comparison to the neutral word-picture pairs (facilitation) and whether unrelated word-picture pairs resulted in slower reaction times in comparison to neutral word-picture pairs (interference). We further examined whether these effects (if any) map onto response conflict or aspects of target processing. In addition, identity (‘man’, ‘woman’) and associative (‘tie’, ‘dress’) primes were introduced to investigate the cognitive mechanisms of semantic and Stroop-like effects in response priming (introduced respectively by associations and identity words). We analyzed responses and reaction times using the drift diffusion model to examine the effect of facilitation and/or interference as a function of the prime type. We found that regardless of prime type words introduce a facilitatory effect, which maps to the processes of visual attention and response execution.